EDUKASI KEAMANAN PANGAN DI KANTIN KAMPUS PUTRI UNIDA GONTOR - kartika pibriyanti; Ardiani Ayu Puspitarini; Lulu Luthfiya; Oktavia bela Dyah Ajeng Panganti; Erika Anggraini Lintang; Rahma Ningrum; Rahayu Wulan Safitri (Universitas Majalengka, 2023)
Background Food service has the basic principles of hygiene and health in the provision of food, the food served must be free from all kinds of contamination. The canteen is a crucial type of place where food is served. The purpose of the activity is to provide food safety education to canteen managers. Methods this activity uses an outreach method with poster media and questions and answers, then pre-test before education and post-test after education is carried out followed by statistical analysis with paired samples test. Result there is an increase in the knowledge of workers after education as evidenced by the results of statistical analysis, a significance value of 0.044. Conclusion there is an effect of education on increasing the knowledge of UNIDA Gontor canteen managers on the female campus.